Effect of drying, storage temperature and air exposure on astaxanthin stability from Haematococcus pluvialis. (August 2015) - Ahmed, Faruq; Li, Yan; Fanning, Kent; Netzel, Michael; Schenk, Peer M.
Abstract: Astaxanthin is a powerful antioxidant with various health benefits such as prevention of age-related macular degeneration and improvement of the immune system, liver and heart function. To improve the post-harvesting stability of astaxanthin used in food, feed and nutraceutical industries, the biomass of the high astaxanthin producing alga Haematococcus pluvialis was dried by spray- or freeze-drying and under vacuum or air at − 20 °C to 37 °C for 20 weeks. Freeze-drying led to 41% higher astaxanthin recovery compared to commonly-used spray-drying. Low storage temperature (− 20 °C, 4 °C) and vacuum-packing also showed higher astaxanthin stability with as little as 12.3 ± 3.1% degradation during 20 weeks of storage. Cost-benefit analysis showed that freeze-drying followed by vacuum-packed storage at − 20 °C can generate AUD600 higher profit compared to spray-drying from 100 kg H. pluvialis powder. Therefore, freeze-drying can be suggested as a mild and more profitable method for ensuring longer shelf life of astaxanthin from H. pluvialis . Highlights: Freeze-drying led to higher astaxanthin recovery from microalgae than spray-drying. Freeze-drying can increase the shelf life of astaxanthin. Storage below 4 °C and vacuum packing showed higher astaxanthin stability. Freeze-drying and vacuum-packed storage at − 20 °C can generate higher profits.